COMPARISON OF EFFECTS OF MASSAGE THERAPY ALONE AND IN COMBINATION WITH GREEN COCONUT WATER THERAPY ON B-ENDORPHIN LEVEL IN TEENAGE GIRLS WITH DYSMENORRHEA - Fitria Hikmatul Ulya; Agus Suwandono; Ida Ariyanti; Ari Suwondo; Suryati Kumorowulan; Sri Endang Pujiastuti (Belitung Nursing Journal, 2017)
Background: Dysmenorrhea is pain during menstruation in lower abdomen, and is not due to other diseases. Effleurage massage and consuming green coconut water are considered able to reduce menstrual pain. However, little is known about the effect of the combination between the two interventions. Objective: To compare the effectiveness of effleurage massage and in combination with green coconut water on pain, anxiety, and ß-endorphin level in teenage girls with menstrual pain (dysmenorrhea). Design: A quasi-experiment with pretest-posttest approach design with control group. There were 36 samples recruited in this study by purposive sampling, which were divided into a massage therapy group, the combination therapy group, and a control group. Menstrual pain was measured using Numeric Rating Scale, while anxiety was measured using Zung Self rating Anxiety Scale (ZSAS), and endorphin level using ELISA (Enzyme-Linked Immunosorbent Assay). One-way ANOVA test and repeated ANOVA were performed as a bivariate analysis. MANCOVA and post hoc ANOVA were used for multivariate analysis. Result: The combination of massage and green coconut water was more effective in reducing pain (p 0.013) and anxiety levels (p 0.000), and in increasing β-endorphin (p 0.029) with significant value of <0.05 compared to the massage therapy alone. Conclusion: The combination of effleurage massage and green coconut water had significant effect in decreasing anxiety and pain levels, and increasing β-endorphin levels in teenage girls with painful periods (dysmenorrhea); and more effective than performing effleurage massage only. It is suggested that this combination therapy could be used as an alternative therapy for women with dysmenorrhea.